Eight gigayears of galaxy mergers - Robaina Rapisarda, Aday (2010)
Galaxy interactions are expected to play a crucial role in the build--up of stellar mass in any cold dark matter cosmology. Of particular interest are the mergers between systems of a comparable mass, as they are predicted to be one of the main modes of galaxy growth and have a crucial impact in the shaping of galaxy morphologies and dynamics. In this thesis I study two key aspects of the role that mergers play in galaxy evolution: a) What is the contribution of major galaxy interactions to the star formation history of the Universe at z < 1?, and b) How important are galaxy interactions for the build--up of the massive end of the red sequence? To answer the first question I use photometric redshifts, stellar masses and UV star formation rates from COMBO-17, 24 microns star formation rates from Spitzer and galaxy morphologies from two deep Hubble Space Telescope cosmological survey fields to study the enhancement in star formation activity as a function of galaxy separation ...
Online publiziert: 2010
Keywords: Hochschulschrift; Entstehung; Galaxie